ANALISIS FAKTOR REPURCHASE INTENTION KONSUMEN KOI THE JAKARTA - Adveni, Lusia Vreyda; Monica, Yossy Silviani (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Companies must be able to understand consumer behavior, so that companies can retain consumers to become regular customers. Repurchase is one of the causes of company survival. Companies can spend much less money on advertising and marketing if the company is able to build long-term relationships with customers, it is hoped that customers will continue to look for the products they have consumed and can spread news about these products to other people (Andrew, 2012). What is examined in this research are the factors that cause repurchase intention for contemporary beverage products at KOI ThÃ© as one of the first bubble tea pioneers in Indonesia. This research uses a quantitative approach method. This type of research is factor analysis. In this research, the sampling technique used is. nonprobability sampling with purposive sampling technique with the number of samples in this study being 135 people. In this writing, data collection techniques were used by distributing questionnaires (questionnaires) with a Likert scale. The factors that influence consumers'